PENGARUH TRADING VOLUME ACTIVITY, CASH FLOW OPERATION, RETURN ON ASSETS, CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP RETURN SAHAM PADA PERUSAHAAN SEKTOR PROPERTI DAN REAL ESTATE DI BEI PERIODE 2010–2014 - Winari, Ashi Aretha; Wahyudi, Sugeng (Diponegoro Journal of Management, 2016)
Stock returns is one motivator in a process of investment, then the measurement of stock returns is a way that is often used by investors to compare different investment alternatives, thus allowing investors to determine its success in making an investment. This study was conducted to determine the extent of Trading Volume Activity (TVA), Cash Flow Operation (CFO), Return on Assets (ROA), the Current Ratio (CR) and Debt to Equity Ratio (DER) affect stock returns in property and real estate sectors.The method used is descriptive and verification methods, to address issues regarding all the variables independently sampling method using purposive sampling method. Of the forty-five companies, only thirty-nine companies included in the study sample.Activity (TVA), Cash Flow Operation (CFO), does not significantly influence stock return. But Return on Assets (ROA), the Current Ratio (CR) significantly affect stock returns in which the value is more than 0.05.